Frequency and prognostic impact of mid-expiratory flow reduction in stable patients six months after hospitalisation for heart failure with reduced ejection fraction. (15th January 2017) - Brenner, Susanne; Christa, Martin; Berliner, Dominik; Deubner, Nikolas; Ertl, Georg; Held, Matthias; Marx, Almuth; Angermann, Christiane E.; Störk, Stefan; Rutten, Frans H.; Güder, Gülmisal
Abstract: Aim: This study investigates the prevalence and prognostic impact of central and small airways obstruction (CAO and SAO) in patients with stable heart failure (HF). Methods & results: Spirometry was performed in 585 outpatients (mean age 65 ± 12 years, 75% male) six months after hospitalisation for acute decompensation secondary to HF with ejection fraction < 40%. We assessed forced expiratory volume in the first second (FEV1), forced vital capacity (FVC) and mid-expiratory flow (MEF) at 50% of FVC. CAO was defined by FEV1/FVC < 0.7. SAO was defined by FEV1/FVC ≥ 0.7 plus MEF < 60% of predicted value. CAO and SAO were excluded in 359 patients (61% of all). MEF < 60% predicted was found in 226 patients (39% of all), among those 88 with CAO (15% of all) and 138 (24% of all) with SAO. During a twelve month follow-up, 42 patients (7.2%) died. Mortality rates of patients with CAO and SAO were comparable (12.5% and 10.9%, respectively, p = 0.74), and both higher than in patients without airways obstruction (4.5%, both p < 0.01). In univariable Cox regression analysis, both CAO and SAO were associated with 2-fold increased all-cause mortality risk (hazard ratios [95% confidence intervals]: 2.78 [1.33–6.19], p = 0.007 and 2.51 [1.24–5.08], p = 0.010, respectively). Adjustment for determinants of CAO and SAO, prognostic markers of heart failure and comorbidities attenuated the association of mortality with CAO but not with SAO. Conclusions: SAO is more common than CAO and indicates an increased mortality risk in HF. Thus, reduced MEF may be a feature of patients at risk and merits special attention in HF management.